Protective Effect of Anthocyanidins on Astrocytes and Apoptosis Induced by Oxidative Damage - López, Ana; Palomino, Olga; Ortega, Teresa; Carretero, Emilia (Planta Medica Letters, 2015)
As a result of the longer life expectancy in the human population, neurodegenerative diseases are increasing, so finding effective treatments together with prevention strategies are urgently needed. Anthocyanins are polyphenolic compounds from vegetal species that have shown strong antioxidant and anti-inflammatory activities in various experimental models. The effect of the anthocyanidins cyanidin, malvidin, and pelargonidin at different concentrations (5 to 100 µM) on experimental models of cell oxidation and apoptosis was studied and compared with the positive control Trolox. The human astrocyte glioblastoma, cellular line U373, was used for a cellular injury model using Fentonʼs reagent (0.5 mM FeSO4/1 mM H2O2) and to measure the lactate dehydrogenase enzyme activities and lipid peroxidation level (thiobarbituric acid reactive substances) by fluorimetric analysis and malondialdehyde release by HPLC. Also, caspase 3, 8, and 9 activities were measured by fluorimetric analysis. The results show that the studied anthocyanidins are able to revert the induced apoptosis related to caspase activation and lipid peroxidation. All the assayed anthocyanidins significantly decreased the activation of caspases 8 and 3, although malvidin and cyanidin increased the activity of caspase 9 when compared to non-treated cells.
Keywords: antioxidant; neuroprotection; anthocyanidins; cyanidin; pelargonidin; malvidin; oxidative stress